Efeito do fósforo no desenvolvimento inicial de plantas de mogno-africano - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
Is increasingly important to the development of sustainable and highly productive forest stands that meet the growing demand for timber and protect native forest resources. In this way, studies that determine the nutritional requirements that cause in increased productivity, encourage the deployment of commercial forests. The objective of this work was to determine the ideal dose for the initial development of African mahogany. The experiment was conducted in a greenhouse. After collecting, analyzing and incubation of soil treatments with phosphorus were distributed into pots with 7dm3 capacity, being they: 0, 50, 100, 150 and 200 mg dm-3. During the experiment the water retention capacity was maintained at 60 and at the end of the experiment the variables height, number of leaflets, neck diameter, leaf dry mass, root and stem, total dry mass, efficiency of use and levels of phosphorus in the foliage were measured. The observed data were subjected to analysis of variance and when significant subjected to regression analysis. Height, diameter, number of leaflets, dry mass of leaves, stem, root and total dry mass showed statistical differences by adjusting the polynomial regression models. The medium, in most cases, showed most growth in the range of 150 mg dm-3, with a decreasing effect after the ideal doses, reducing the development of species in the early stages. The inferences of reasons of root, stem, leaf mass and nutrient use efficiency showed no statistical differences between the treatments studied. The results observed show that the phosphorus is fundamental in the development of the species studied, demonstrating the demand for plants of mahogany to macronutrient tested by promoting significant increments in the early stages of development.
Keywords: Khaya senegalensis; adubação fosfatada; crescimento; Khayasenegalensis; fertilization; growth; CIENCIAS AGRARIAS